1993
DOI: 10.1017/s0515283600042256
|View full text |Cite
|
Sign up to set email alerts
|

Size for Gestational Age and Neonatal Sleep Variables: Behavioral Indices of Risk in Fullterm Twins

Abstract: Neonatal sleep behaviors and behavioral state cycling were observed for 20 pairs of same-sex, fullterm twins in which one twin of the pair was appropriate-for-gestational-age (AGA) and the other twin was small-for-gestational-age (SGA). Time-sampling recordings were made in active sleep of number and vigor of limb movements, body and head movements, and mouth movements. No group differences were observed for time spent in first active sleep, first quiet sleep, or length of first sleep cycle. Examination of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Despite their common intrauterine experience, twins may show differences in activity, irritability, resistance to soothing, and sleeping behavior (Riese, 1993(Riese, ,1994. Such similarities and differences can be partially explained by whether the twins are monozygotic or dizygotic because identical twins presumably share more common behavioral traits than do fraternal twins.…”
mentioning
confidence: 99%
“…Despite their common intrauterine experience, twins may show differences in activity, irritability, resistance to soothing, and sleeping behavior (Riese, 1993(Riese, ,1994. Such similarities and differences can be partially explained by whether the twins are monozygotic or dizygotic because identical twins presumably share more common behavioral traits than do fraternal twins.…”
mentioning
confidence: 99%
“…With few exceptions (e.g., Berker, Goldstein, Lorber, Priestley, & Smith, 1992; Hay & O’Brien, 1987; Riese, 1988, 1993), researchers have focused on the role of a single early risk factor—birth weight—in modifying developmental outcome. The findings of several studies revealed that the twin with the higher birth weight tends to fare better intellectually (Churchill, 1965; Marsh, 1980; Matheny & Brown, 1971; Scarr, 1982; Willerman & Churchill, 1967), or that “the bigger the better” (Scarr, 1982, p. 236).…”
mentioning
confidence: 99%